Digital System in Supply Chain for Elderly Care Management in Thailand - Artaphon Chansamut (International Journal of Supply Chain Management, 2023)
The review article title digital system in supply chain for elderly care management in Thailand aim to present tax management through a supply chain applying for better effective tax management The elderly care management needs to be appropriate to changes of globalized economy and society. The processes consisted of Suppliers, Government organization , Satisfaction and service , Customer, Satisfaction and feedback .All element connect with digital in the Thailand with the supply chain. This truly added the society in Thailand .The supply chain will be applicable for elderly care in Thailand.